Autumn Hebert

2023-02-28

How to find $f(-3)$ given $f\left(x\right)=2x+2$?

repicotit48p

Beginner2023-03-01Added 3 answers

Given solution: Simply substitute the value of $-3$ given. In other words, $f(-3)$ is the function of $f\left(x\right)$, however in this case, $x$ is $-3$

$f(-3)=2(-3)+2$

Distribute $2$ through the parenthesis

$f(-3)=-6+2$

Simplify

$f(-3)=-4$

$f(-3)=2(-3)+2$

Distribute $2$ through the parenthesis

$f(-3)=-6+2$

Simplify

$f(-3)=-4$

Dillan Perez

Beginner2023-03-02Added 6 answers

We could replace $-3$ for $x$ and simplify:

$f\left(x\right)=2x+2$

$f(-3)=2(-3)+2$

$f(-3)=-6+2$

$f(-3)=-4$

So $f(-3)=-4$.

$f\left(x\right)=2x+2$

$f(-3)=2(-3)+2$

$f(-3)=-6+2$

$f(-3)=-4$

So $f(-3)=-4$.